A theory-ingrained integrated change management framework for the implementation of Enterprise Resource Planning Systems to mobilise user readiness - Van der Merwe, Alta J. (University of Pretoria, 2022)
Thesis (PhD (Information Technology))--University of Pretoria, 2020.